R*-I-Lc-Continuous Functions in an Ideal Space - Josephine christilda, A.; Manoharan, R. (International Journal of Engineering and Technology, 2018)
Â  Some new sets like of â€œR*-LC-setsâ€, â€œR*- I-LC-setsâ€ are introduced using R*-topology. Also defined the notions of â€œR*- I-LC-continuous mapsâ€, â€œI*R- continuous mapsâ€, â€œgÂ-R*- continuous mapâ€s and represent â€œ*-continuous functionâ€ as decomposition two newly defined functions.Â Â Â